The Determinant Factors of Supply Chain Management on Purchase Intention of an International Branded Apparels Status Quo - Rozita Naina Mohamed; Bahtiar Mohamad; Halimahton Borhan; Idris Osman; Surianor Kamaralzaman (International Journal of Supply Chain Management, 2019)
The purpose of this study is to investigate the factors influencing status quo of supply chain purchase intention of international branded apparel items among young adult in Malaysia. Data for this study have been collected using self-administered questionnaire which distributed to the channel members (young adult retailers) and customers by using a convenient sampling method. A total of 100 completed and usable surveys were collected. Pearson Correlation analysis and multiple regression analysis have been used to determine the interrelation between different variables in the intention to purchase. The results of this study are limited by the number of participants, thus the area and location of the study and the absence of other methods for obtaining results other than questionnaires. Empirical results show that there is a significant correlation between independent variables (perceived quality, brand image, word of mouth, self-concept and need for uniqueness) towards the dependent variable (purchase intention). This study is important to the marketers to understand the factors that influence consumers purchase intention. Marketers could also improve their business and strengthen it based on a selected variable to be more competitive.